Defaulting on Water Utility Bills: Evidence from the Greater Accra Region of Ghana - Sualihu, Mohammed Aminu; Arifur Rahman, M. (Indian Journal of Finance, 2014)
Water utility companies, especially those operating in low-income countries, write off millions of dollars in bad debts due to non-payment of bills by customers. Delayed payments and outright non-payments are increasingly constraining utilities’ revenue performance and their service provisions. The aim of the present study is to examine the effects of a set of behavioural and institutional factors on the likelihood of defaulting on water bills. Based on a survey of households in the Greater Accra Region of Ghana (GARG), our empirical analysis suggests that an improvement in institutional factors such as monitoring and control measures and behavioural factors such as service quality, service value, and corporate image has a significant effect in minimizing the likelihood of payment default. Other factors considered in the analysis - transaction time, billing issues and customer satisfaction - do not seem to have an effect on estimated default likelihood. We provide detailed discussion and policy implications of our findings.